LOW CARBON DEVELOPMENT STRATEGY FOR LAND USE SECTOR IN CILIWUNG MIDDLE-STREAM WATERSHED - Sularso, Gamma Nur Merrillia; Tambunan, Rudy P.; Atmoko, Andreo W. (Secretariat of Forestry Research and Development Agency, 2015)
The second (2nd) and third (3rd) segment of Ciliwung middle-stream watershed land use have changed drastically over the past two decades. This paper analyses the land use change from 1989-2012 and its impact on decreasing carbon stock or increasing CO2eq emission, as well as to establish projected Reference Level (RL) to 2020. Best RL projection was used to establish the Low Carbon Development Strategy (LCDS) in both segments. The land use changing from 1989-2012 indicated a reduction of green space area by 2,575.57 ha whereas the non-green space area increased by 2,575.57 ha. These changes decreases the carbon stock by 26,900 ton C and released CO2eq emission by about 98,723 ton CO2eq. Population growth, demand on land and land constraints were found to be the driving factors of land use changes in this area. Reference Level 2020 was established based on business as usual (BAU) and forward looking (FL) scenarios. The projection showed that FL was the best scenario which estimated carbon storage at 217,610 ton C in 2020. Low carbon development strategy directed to the area of green space added up to 20% carbon storage through the implementation of the strategy based on green space and non-green space which covered the areas from protection, supervision, extension or awareness and law enforcement.